Critical social work with unaccompanied asylum-seeking young people: Restoring hope, agency and meaning for the client and worker. (May 2017) - Nelson, Deborah; Price, Elizabeth; Zubrzycki, Joanna
This article presents a model of Australian social work with unaccompanied asylum-seeking young people which aims to build hope, agency and meaning for the social worker and the young person. Informed by Foucault's understanding of resistance, the model encourages social workers to pay attention to little practices of freedom through the development of professional relationships which address counselling needs, practical advocacy and social change within complex socio-political, cultural and therapeutic contexts. A case vignette of 'Ali' applies the model in practice. The article concludes with an exploration of the model's potential for international transferability.